The Effect of UTAUT and IRT Factors on the Digital Fishery Platforms Acceptanc - Purwanto, Edi; Sjarief, Rachman; Anwar, Chaerul (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2021)
The background of this research is the weakness of the marine product supply chain which reduces the interest of the Indonesian people to consume abundant fish. The purpose of this study was to examine the effect of UTAUT and IRT factors on digital fishery platform acceptance. The study was conducted in the provinces of Banten and West Java using a convenience sampling technique. The data collected were 240 samples, consists of 151 samples from Banten province, and 89 samples from West Java province. The results of the study prove that three UTAUT factors, namely performance expectancy, effort expectancy, and social influence significantly affect the intention to use digital platforms. Three IRT factors have a significant effect on resistance to using digital platforms. However, this study also shows low resistance and high acceptance on the digital fishery platform, so that the effect of resistance on the intention to use digital fishery platforms is proven to be negative and significant. The novelty of this research is the combination of UTAUT and IRT theory on digital platform acceptance. The practical benefits of this research can be used as a basis for decision-making to build a digital fishery platform that will benefit marine fish consumers and fishermen.